EFL Students’ Willingness to Communicate: A Survey of Verbal Participation in Speaking Classes - Lulu Jola Uktolseja (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
In English as a Foreign Language (EFL) course, students' verbal engagement is considered to be greatly influenced by their willingness to communicate (WTC). However, many students continue to hesitate during speaking practice because they are nervous, lack confidence, and fear making mistakes. The purpose of this study was to characterize the level of verbal participation and communication readiness of EFL students in speaking classes. A quantitative descriptive survey design was used in this study, which involved fifty EFL students who attended speaking classes. A 15-item Likert scale questionnaire measuring students' readiness to speak, respond, initiate communication, and participate in speaking exercises was used to collect data. Descriptive statistics, such as mean scores for each item, were used to analyze the data. With an overall average score of 3.73, the results of the study show that students' general readiness to communicate is classified as high, indicating a generally positive attitude toward speaking activities. Students' love of speaking activities received the highest score, while elements related to spontaneously initiating conversation received slightly lower scores. Additionally, this study provides empirical data on the average of students' communication willingness, which has practical consequences for EFL teachers creating instructional strategies that encourage increased verbal involvement.